Moonflower murders : a novel - Horowitz, Anthony, 1955- (Horowitz, Anthony, 1955- Susan Ryeland, 2020)
"Farlingaye Hall is a beautiful hotel in Suffolk on the east coast of England. Unfortunately, it is also the site of the brutal murder of Frank Parris, a retired advertising executive. Stefan Codrescu, a Romanian maintenance man, is arrested after police find blood spatter on his clothes and bed linen. He is found guilty and spends eight years in prison. It appears an open and shut case, but there is more than meets the eye. Alan Conway, the late author of the fictional Magpie Murders, knew Frank Parris and once visited Farlingaye Hall. Conway based Atticus Pund Takes the Cake, the third book in his detective series, on the hotel. Cecily Treherne, the daughter of the hotel owner, read the book and believes the truth of Stefan's innocence is found in its pages. But now...she has disappeared. Conway's former editor Susan Ryeland leaves her own hotel in Crete and travels to Suffolk to investigate the murder and Treherne's disappearance"--